Demokrasi di Indonesia terhadap Mangkunegaran: Memudarnya Politik Kekuasaan Kraton - Sunarmi Sunarmi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
Mangkunegaran in early establishment initially had a capacity and authority armed with forces and territory, which currently only deemed as one of the cultural guardian institution even more physically interpreted as a cultural heritage object. The inability of Mangkunegaran to dampen the Anti-Swapraja Movement is actually the beginning for waning power politics in Mangkunegaran in the royal system with the doctrine of keagungbinataraan. Declarations to declaration issued by KGPAA Mangkunegara VIII to face the Anti Swapraja movement was compeletely ignored by the society. In traditional Javanese life, it is signed by oncate (the loss of) wahyu kedhaton of Mangkunegaran. In the end the Swapraja Region in Surakarta was revoked, Mangkunegaran has no authority as the center of government.